Pengembangan Lembar Kerja Peserta Didik (LKPD) Biologi Berbasis Pendekatan Scientific Materi Sistem Ekskresi Pada Manusia Kelas VIII SMP Negeri 2 Maumere - Krisna Pada; Yohanes Bare; Sukarman Hadi Jaya Putra (Peneliti.net, 2021)
Development in science and technology have a great influence in various aspect of human life. One of the aspectcs is education which is an inseparable part of the process of human maturation that needs to take advantage of advances in science and technology in order to be able to achieve goals effectively and efficiently. The lack of student participation in biology material like excretory system makes the expression material seen as difficult. This research study aims to develop a Biology Learning Based on a Scientific Approach to Human Excretion System Materials for Class VIII SMP Negeri 2 Maumere. The development model used is a 4D model. The results showed that the worksheets developed were declared valid by material experts, media experts and linguists. The LKPD being tested has criteria that fit the category that is appropriate for use in the excretory system at SMPN 2 Maumere.